Criminal Acts in the Process of Online Loan Collection - Adhitya Narendra Dwipa (Green Publisher Indonesia, 2024)
Online lending is an innovation in finance that utilizes information technology to facilitate transactions between borrowers and lenders without meeting in person. While this generally goes smoothly, problems often arise if there are late payments, particularly in collection practices. Many reports mention unethical, intimidating, and unlawful collection practices, which harass consumers. This research aims to identify and analyze legal protection for criminal acts in the online loan collection process, as well as analyze the decision of the North Jakarta District Court Number 438/Pid.Sus/2020/PN Jkt.Utr. The research method used is normative legal research with a statutory approach, using literature study as a data collection technique, which is then analyzed in three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that repeated billing via text messages and telephone before the due date violated the billing code of ethics in the POJK on Consumer Protection in the Financial Services Sector. In addition, POJK 10/2022 states that organizers are not allowed to make direct collections if the delay exceeds 90 days from the due date. Legal collection by debt collectors that do not comply with the rules, especially in the case of illegal online loans, can be subject to Article 45 paragraph (4) Jo Article 27 paragraph (4) of the ITE Law, Article 368 of the Criminal Code, and Article 369 of the Criminal Code. Thus, these regulations can provide legal protection to consumers in the face of criminal acts when online loan collection occurs.